(untitled) (International Journal of Nursing Education, 2022)
OSCEs are a form of simulation and are often collective but may be determinative. This educational tactic requires robust design based on sound pedagogy to assure practice and evaluation of holistic nursing care. The OSCE, first used in the 1970s, is an assessment of capability carried out in a well-planned, arranged and objective way. Summative OSCEs are often used at the end of courses or programmes or on accomplishment of a module to test students in contradiction of set objectives and learning consequences. OSCE is used in different areas like history taking skills, interpersonal and communication skills, Mental Health Assessment, clinical diagnosis making, clinical problem-solving skills etc. Preparation is vital and increases students’ self-confidence in performing skills during the OSCE and in clinical areas. The OSCE examination entails of about 10-15 stations, each of which requires about 4-5 minutes. The number of stations and time consumed on each station may vary based on needs of evaluation. Thus, using 15 stations of 4 minutes separately, 15 students can complete the examination within 1 hour. The OSCE style of clinical evaluation, given its obvious advantages, specifically in terms of objectivity, standardization and resourcefulness of clinical scenarios that can be measured, shows superiority over so called clinical assessment methods especially in medical fields majorly in nursing practices.